Raymie nightingale [compact disc, unabridged] - DiCamillo, Kate (Listening Library, 2016)
Raymie Clarke decides that if she can win the Little Miss Central Florida Tire competition, then her father, who left town two days ago with a dental hygienist, will see Raymie's picture in the paper and (maybe) come home. To win, not only does Raymie have to do good deeds and learn how to twirl a baton; she also has to contend with the wispy, frequently fainting Louisiana Elefante, who has a show-business background, and the fiery, stubborn Beverly Tapinski, who's determined to sabotage the contest. But as the competition approaches, loneliness, loss, and unanswerable questions draw the three girls into an unlikely friendship and challenge each of them to come to the rescue in unexpected ways.